Wellbeing Through Humanism : Devising an Alternative Barometer of Urban Social Progress in Malaysia - Shirly Wong Siew, Ling; Juliana Qarishma, Jublee; Evan, Lau; Tan, Suk Chinn; Mandy Ang Jing, Ying (2022)
Today, there is a growing attention towards a widespread myth that a nation's economic prosperity inevitably leads to its citizens enjoying a greater wellbeing. However, foundation of human wellbeing, especially mental wellness, and life satisfaction of individuals in economically advantaged countries remain fragile. Malaysia, as the third-largest economy in the ASEAN region and has one of the best economic records in the world likewise struggling with unbalanced harmony between economic development and societal progress. Despite government constant effort to strengthen sustainable development of the society, individuals who yet to meet the criteria for flourishing is far and wide, and rates of flourishing is believed to diminish at the presence of COVID-19 pandemic. In view of this, effort to put social progress on par with post-pandemic economic revitalization as well as prosperity of the nation in years to come is undoubtedly imperative. Rooted by the fundamental principle of humanistic economics as well as the nation of collective wellbeing envisioned by the Bhutanese concept of happiness, the present study is motivated develop an alternative barometer of social progress for the urban populace in Malaysia. The Humanistic-Enabled Barometer of Social Progress (H-BSP) blends the philosophical theories of wellbeing, happiness psychology as well as neoclassical and welfare economics into the creation of a holistic metrics of social progress. The realization of the H-BSP yardstick serves as a critical move towards a humanized facets of measuring the subjective and non-monetary gains of the growing Malaysian economy.